Knee pain in runners: the most common causes, symptoms, and treatment review - Gizińska, Natalia; Górniak, Aleksandra; Rusiecka, Amelia; Kubas, Aleksandra; Lewandowska, Paulina; Sobczyk, Aleksander; Widawski, Michał (Quality in Sport, 2025)
Introduction and Purpose: Running is one of the most common activities. It is also associated with a high risk of knee joint injuries. The most common are Patellofemoral Pain Syndrome (PFPS), Iliotibial Band Syndrome (ITBS), and Patellar Tendinopathy (PT). These conditions can limit mobility and reduce quality of life. The purpose of this article is to review the causes, symptoms, prevention, and treatment for these conditions in runners, based on the most recent knowledge. State of Knowledge: The most frequent running-related knee injuries are PFPS, ITBS, and PT. An accurate diagnosis is essential for effective treatment. Management should be tailored to everyone, considering factors such as age and the stage of the condition. These injuries often require a break from running. Most cases improve with non-surgical treatments. Surgery is reserved for severe or persistent cases. Preventive strategies focus on addressing training mistakes, strengthening specific muscle groups, and refining running mechanics. Methods: The following paper analyzed studies found on electronic databases, including PubMed, Google Scholar, using keywords such as “knee injury”, “PFPS”, “ITBS”, “PT”, “causes of knee pain”, “treatment of knee injuries”, and “prevention of knee injuries”. Articles include randomized controlled trials, meta-analyses, and systematic reviews prioritizing resources published after 2015. Conclusions: Knee injuries in runners are multifactorial and often result from poor biomechanics, muscle imbalances, training errors, or repetitive strain. Accurate diagnosis is essential to differentiate between conditions with similar symptoms. Conservative treatment is the first-line treatment for PFPS, ITBS, and PT, and it shows good results. Surgery is reserved for treatment-resistant cases. Prevention mainly focuses on correcting training errors, strengthening key muscle groups, and improving running technique, which is a key to reducing the risk of injury.